Production of biofuels from fish wastes: an overview. Issue 3 (4th May 2019) - Yuvaraj, D.; Bharathiraja, B.; Rithika, J.; Dhanasree, S.; Ezhilarasi, V.; Lavanya, A.; Praveenkumar, R.
ABSTRACT: Every year billions of tons of fish waste are produced by fish processing units. These wastes when dumped into the environment cause emissions which in turn degrade the land. An alternative solution for the problem involves their processing into biofuel, pharmacological components, fertilizer and fodder. Biofuel is a trending concept and an alternative for present day fuels. Biofuels are pollution free and thus are advantageous over current fuels. Biofuels are produced from organic waste, seaweed, and micro-algae. The current research on fish wastes for the production of biodiesel is mainly because of their nontoxic and biodegradable nature. Biodiesel produces less air toxins, CO2, hydrocarbons and other particulates when compared to the standard fuel or diesel. The conversion process involves extraction of fish oil from the waste of the fishing industry. The oil is cleaned and purified. With the addition of a catalyst, biodiesel and bio-gas are produced by transesterification and anaerobic digestion respectively. Various results such as Fourier transform nuclear magnetic resonance (FT-NMR), gas chromatography mass spectrometry (GCMS) and proton nuclear magnetic resonance (H-NMR) analysis, and best management practices (BMP) assay show the efficient conversion and working of biofuels.